The Combination of MR Elastography and Proton Density Fat Fraction Improves Diagnosis of Nonalcoholic Steatohepatitis. Issue 2 (25th December 2021) - Alsaqal, Salem; Hockings, Paul; Ahlström, Håkan; Gummesson, Anders; Hedström, Anders; Hulthe, Johannes; Johansson, Lars; Niessen, Heiko G.; Schoelch, Corinna; Schultheis, Christian; Vessby, Johan; Wanders, Alkwin; et al.
Abstract : Background: Nonalcoholic fatty liver disease (NAFLD) is rapidly increasing worldwide. It is subdivided into nonalcoholic fatty liver (NAFL) and the more aggressive form, nonalcoholic steatohepatitis (NASH), which carries a higher risk of developing fibrosis and cirrhosis. There is currently no reliable non‐invasive method for differentiating NASH from NAFL. Purpose: To investigate the ability of magnetic resonance imaging (MRI)‐based imaging biomarkers to diagnose NASH and moderate fibrosis as well as assess their repeatability. Study Type: Prospective. Subjects: Sixty‐eight participants (41% women) with biopsy‐proven NAFLD (53 NASH and 15 NAFL). Thirty participants underwent a second MRI in order to assess repeatability. Field Strength/Sequence: 3.0 T; MR elastography (MRE) (a spin‐echo echo‐planar imaging [SE‐EPI] sequence with motion‐encoding gradients), MR proton density fat fraction (PDFF) and R2* mapping (a multi‐echo three‐dimensional gradient‐echo sequence), T1 mapping (a single‐point saturation‐recovery technique), and diffusion‐weighted imaging (SE‐EPI sequence). Assessment: Quantitative MRI measurements were obtained and assessed alone and in combination with biochemical markers (cytokeratin‐18 [CK18] M30, alanine transaminase [ALT], and aspartate transaminase [AST]) using logistic regression models. Models that could differentiate between NASH and NAFL and between moderate to advanced fibrosis (F2–4) and no or mild fibrosis (F0–1), based on the histopathological results, were identified. Statistical Tests: Independent samples t ‐test, Pearson's chi‐squared test, area under the receiver operating characteristic curve (AUROC), Spearman's correlation, intra‐individual coefficient of variation, and intraclass correlation coefficient (ICC). Statistical significance was set at P  < 0.05. Results: There was a significant difference between the NASH and NAFL groups with liver stiffness assessed with MRE, CK18 M30, and ALT, with an AUROC of 0.74, 0.76, and 0.70, respectively. Both MRE and PDFF contributed significantly to a bivariate model for diagnosing NASH (AUROC = 0.84). MRE could significantly differentiate between F2–4 and F0–1 (AUROC = 0.74). A model combining MRE with AST improved the diagnosis of F2–4 (AUROC = 0.83). The ICC for repeatability was 0.94 and 0.99 for MRE and PDFF, respectively. Data Conclusion: MRE can potentially diagnose NASH and differentiate between fibrosis stages. Combining MRE with PDFF improves the diagnosis of NASH. Level of Evidence: 2 Technical Efficacy: Stage 2